6) [tex] \frac{3}{2}x+ \frac{1}{2} [/tex]
f(-1)=[tex] -\frac{3}{2} + \frac{1}{2} =- \frac{2}{2} =-1[/tex]
f(0)=[tex]0+ \frac{1}{2} = \frac{1}{2} [/tex]
f(1)=[tex] \frac{3}{2} + \frac{1}{2} = \frac{4}{2} =2[/tex]
f(2)=[tex] \frac{6}{2} + \frac{1}{2} = \frac{7}{2} [/tex]
f(3)=[tex] \frac{9}{2}+ \frac{1}{2}= \frac{10}{2}=5 [/tex]
7)[tex] \frac{10-2x}{5} [/tex]
f(0)=[tex] \frac{10}{5}=2 [/tex]
f(1)=[tex] \frac{8}{5} [/tex]
f(2)=[tex] \frac{6}{5} [/tex]
f(3)=[tex] \frac{4}{5} [/tex]
f(4)=[tex] \frac{2}{5} [/tex]
f(5)=[tex] \frac{0}{5} =0[/tex]
h(x)=[tex] \sqrt{3} [/tex]
h:(-2,+∞)→R
∀x∈(-2,∞), h(x)=[tex] \sqrt{3} [/tex]
g(x)=[tex] \frac{1}{3} x[/tex]
g:(-∞,3]
pt x∈(-∞,3] ,[tex] \frac{1}{3}x [/tex], x∈(-∞,1]